Pengaruh Profitabilitas, Likuiditas, Arus Kas Bersih, Kebijakan Deviden dan Ukuran Perusahaan terhadap Harga Saham : (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024) - Mira Rosmala; Andri Andri (BADAN PENERBIT STIEPARI PRESS, 2025)
Abstract This study was conducted to determine the effect of profitability, liquidity, net cash flow, dividend policy and company size on stock prices in manufacturing companies listed on the Indonesia Stock Exchange. The population of this study were all manufacturing companies listed on the Indonesia Stock Exchange totaling 144 companies. The sampling method used purposive sampling method so that the sample used in this study was 22 companies, and the type of data used secondary data, the data collection method used documentation method and the data analysis method was by using multiple regression analysis, hypothesis testing and coefficient of determination. Data analysis based on multiple linear regression analysis where the variables profitability, liquidity, net cash flow and company size have a positive effect while dividend policy has a negative effect on stock prices where the following multiple linear equation is obtained Y = -7.143 + 0.050X1 + 0.001 X2 + 0.127X3 - 0.003X4 + 0.367X5 + e. Partial Test (t-test) where the profitability and company size variables affect stock prices while the liquidity, net cash flow and dividend policy variables do not affect stock prices. In the F test (simultaneous test) the independent variables (profitability, liquidity, net cash flow, dividend policy and company size) together have a significant effect on the dependent variable (stock price). In the determination coefficient test (adj R2) that the dependent variable can be explained by the independent variables with an adj R2 value of 54.5% while the remaining 45.5% is influenced by other variables not examined in this study